Flipped learning and motivation at the University classroom - García Gómez, Antonio (Pulso. Revista de educación, 2016)
In the flipped classroom, students are required to come to class prepared. More precisely, students’ first exposure to the basic course content takes place before class and students actively apply the course content in class. This research aims to explore the benefits of a flipped learning approach (i.e. Just-in-Time Teaching) for university students. In particular, the aim is to investigate whether or not Just-in-Time Teaching accelerates learning and keep students’ motivation high. Using two groups of university students, it was attempted to carry out a systematic qualitative and quantitative analysis to offer an account of this two-fold aim. The analysis reveals that Just-in-Time teaching not only engages university students more, but also they learn more effectively.